THE RELEVANCE OF USING THE INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE PROCESS OF FORMING CULTURAL COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS - Nataliia Grechanyk ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
It is claimed that currently the information technologies have a significant didactic potential, which allows to incentivize students to achieve personal goals in education, including in the acquisition of cultural competences. The aims and objectives of higher pedagogical education provided for by current educational standards include the mastering the basic knowledge and skills, including cultural competency, which is particularly relevant to primary school teachers in the framework of the increasing trend towards globalization.